Questioning the Ecological Footprint. (October 2016) - Galli, Alessandro; Giampietro, Mario; Goldfinger, Steve; Lazarus, Elias; Lin, David; Saltelli, Andrea; Wackernagel, Mathis; Müller, Felix
Highlights: 10 key questions concerning the Ecological Footprint are asked. The questions are answered from a critical and a supporting viewpoint. Overall, discussion and clarity regarding indicators and their representation of sustainability is needed and should be continued. Abstract: In this perspective paper a critical discussion about the concept of the Ecological Footprint is documented based on 10 questions which are answered from critical and supporting points-of-view. These key questions are directed toward the underlying research objectives of the approach, a comparison with similar concepts, the quantification methodology and its accuracy, the characteristics of the observed flows, the role of scales and resolutions, the implementation of food security, the utility of the ecological footprint for society, the political relevance of the concept and the differences from other international indicator systems.